2021
DOI: 10.1111/1365-2745.13800
|View full text |Cite
|
Sign up to set email alerts
|

A whole‐plant economics spectrum including bark functional traits for 59 subtropical woody plant species

Abstract: 1. The whole-plant economics spectrum (PES) refers to the trade-offs among the many plant functional traits that are commonly used as indicators of major adaptive strategies, thereby providing insights into plant distributions, ecosystem processes and evolution. However, there are few studies of what may be called the whole-PES that integrates bark, wood and leaf functional traits for different leaf types and growth habits (evergreen vs. deciduous species).2. To address this gap in our knowledge, 6 bark traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 88 publications
(113 reference statements)
1
33
0
Order By: Relevance
“…Numerous studies have found that plant resource utilization strategies are complex due to their regulation by a combination of environmental factors ( Huang et al, 2021 ; Wang et al, 2022 ). Exploring the distribution patterns of key leaf functional traits at large scales is of great ecological importance to quantify the effects of environmental conditions on plant resource utilization strategies ( Li et al, 2022 ). Based on field survey data from 163 sites in China, we sought to identify the key drivers affecting leaf resource utilization strategies at different vegetative levels in forest communities.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have found that plant resource utilization strategies are complex due to their regulation by a combination of environmental factors ( Huang et al, 2021 ; Wang et al, 2022 ). Exploring the distribution patterns of key leaf functional traits at large scales is of great ecological importance to quantify the effects of environmental conditions on plant resource utilization strategies ( Li et al, 2022 ). Based on field survey data from 163 sites in China, we sought to identify the key drivers affecting leaf resource utilization strategies at different vegetative levels in forest communities.…”
Section: Introductionmentioning
confidence: 99%
“…( 2022) of the study found that the temperature rise, is lower than that of leaf area, chlorophyll content and stomatal density and stomatal area, belongs to the typical type of quick investment return, in contrast to the results of this study, the reason may be that Zhu's (2018) sampling locations for the city, the plant's strategic strategy may be affected by air pollution in cities. In addition, Li (2021) confirmed in his experiment that air pollution would have an impact on strategic strategies. The experiment of low altitude for the arid valley area, water also is the main limiting factors of plant growth, Chen (2021) found that in low water plant to quickly get to adapt to the environment, similar to the results, showed that plant under the condition of water restrictions, tends to raise the utilization ratio of nutrient and moisture retention rate structure (Yang et al .…”
Section: Influence Of Altitude On Strategy Spectrum and Strategic Spe...mentioning
confidence: 79%
“…Leaf veins mainly play a supporting and transport role (Zhang et al .,2017). Studies on functional trait profiles of leaves are still mainly focused on leaf strategic profiles, which aim to study species ecological niche differentiation and coexistence mechanisms (Li et al ., 2021), and there are few studies on the strategic profiles among different tissues of the same organ of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Both across and within these taxa, the associations between multiple wood and bark traits indicate that a conservative-acquisitive stem strategy spectrum is found (cf. Li et al, 2021 ). A stem trait spectrum is also found for each stem compartment.…”
Section: Discussionmentioning
confidence: 99%